2006
DOI: 10.1111/j.1744-6570.2006.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Work–family Conflict and Emotions: Effects at Work and at Home

Abstract: This study investigated the effect of work-family conflict on the emotions of guilt and hostility, and the implications of work-family conflict and these emotions for job satisfaction and marital satisfaction. Using experience-sampling methodology, data were collected from a sample of 75 individuals over a period of 2 weeks (producing 625 data points). Results revealed that within individuals, family-to-work conflict experienced at work, and work-to-family conflict experienced at home, were positively associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
279
1
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(303 citation statements)
references
References 107 publications
18
279
1
5
Order By: Relevance
“…We centered all day-level predictor and control variables (Level 1; e.g., recovery experiences) at the respective person mean (cf. Judge, Ilies, & Scott, 2006), and person-level control variables (Level 2; e.g., trait affect) at the grand mean. Centering day-level variables at the person mean implies that all between-persons variance in these variables is removed, and interpretations of our results referring to stable differences between persons can be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…We centered all day-level predictor and control variables (Level 1; e.g., recovery experiences) at the respective person mean (cf. Judge, Ilies, & Scott, 2006), and person-level control variables (Level 2; e.g., trait affect) at the grand mean. Centering day-level variables at the person mean implies that all between-persons variance in these variables is removed, and interpretations of our results referring to stable differences between persons can be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Benefits associated with the service include the ability to maintain complete anonymity of panelists' identities, which is particularly important in a study dealing with a sensitive topic such as workplace incivility, and the utilization of respondents from various industries and areas, rather than using one research site. Recent studies in the management field have demonstrated that the StudyResponse service is a reliable means of collecting data (Hershcovis & Barling, 2010;Judge, Ilies, & Scott, 2006;Piccolo & Colquitt, 2006;Tepper et al, 2009). …”
Section: Participants and Proceduresmentioning
confidence: 99%
“…It is clear, however, that longer work hours lead to a greater impact on life outside work (Schieman et al, 2009) and increased work-family conflict (Byron, 2005;Michel et al, 2011). The stress and emotional guilt associated with work-family conflict (Judge, Ilies, & Scott, 2006;Morgan & King, 2012), is likely to reduce parental self-evaluations.…”
Section: Work Hoursmentioning
confidence: 99%